2016
DOI: 10.1371/journal.pone.0150911
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Massive Seasonal Aggregations of Blacktip Sharks (Carcharhinus limbatus) in Southeast Florida

Abstract: Southeast Florida witnesses an enormous seasonal influx of upper trophic level marine predators each year as massive aggregations of migrating blacktip sharks (Carcharhinus limbatus) overwinter in nearshore waters. The narrow shelf and close proximity of the Gulf Stream current to the Palm Beach County shoreline drive tens of thousands of sharks to the shallow, coastal environment. This natural bottleneck provides a unique opportunity to estimate relative abundance. Over a four year period from 2011–2014, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…For aquatic ectotherms, seasonal rises in water temperature can act as an important cue in the timing of migration (e.g., salmon [Salmo salar] smolts Jonsson and Ruud-Hansen, 1985;squid [Loliginid forbesi] Sims et al, 2001). All three great hammerheads that exhibited long-distance migrations departed Bimini April to early May when the water temperature began to rise above 26 • C. In the same region, water temperature was found to be a key predictor for the presence and absence of lemon and blacktip shark seasonal aggregations in Florida (Kessel et al, 2014a;Reyier et al, 2014;Kajiura and Tellman, 2016). Future studies on great hammerhead sharks should explore the timing, repeatability, and motivations for such long-distance movements, particularly as their travel routes cross various management and political boundaries.…”
Section: Regional Movements and Return-migrationsmentioning
confidence: 94%
See 3 more Smart Citations
“…For aquatic ectotherms, seasonal rises in water temperature can act as an important cue in the timing of migration (e.g., salmon [Salmo salar] smolts Jonsson and Ruud-Hansen, 1985;squid [Loliginid forbesi] Sims et al, 2001). All three great hammerheads that exhibited long-distance migrations departed Bimini April to early May when the water temperature began to rise above 26 • C. In the same region, water temperature was found to be a key predictor for the presence and absence of lemon and blacktip shark seasonal aggregations in Florida (Kessel et al, 2014a;Reyier et al, 2014;Kajiura and Tellman, 2016). Future studies on great hammerhead sharks should explore the timing, repeatability, and motivations for such long-distance movements, particularly as their travel routes cross various management and political boundaries.…”
Section: Regional Movements and Return-migrationsmentioning
confidence: 94%
“…Dasyatid stingrays dominated the diet of great hammerheads captured in South Africa, Australia as well as in Florida, U.S. (Dodrill, 1977;Stevens and Lyle, 1989;Cliff, 1995). Similarly, in the Jupiter region spawning bait fish, as well as, migration of blacktip sharks, Carcharhinus limbatus and abundance of other small sharks and batoids, likely provide important feeding grounds for great hammerheads (Hueter and Tyminski, 2007;Wiley and Simpfendorfer, 2007;Kajiura and Tellman, 2016).…”
Section: Site Fidelity and Residencymentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true for elasmobranchs and large marine mammals for which measuring variation in densities over various spatial and temporal scales is necessary to gather the information necessary for developing sound conservation and management plans. Over the years, aerial surveys have been extensively used in studies of marine wildlife, particularly to assess their distribution and abundance (Bayliss, ; Hodgson et al , ; Kajiura & Tellman, ; Marsh & Sinclair, ; Pollock et al , ; Rowat et al , ). Recent studies have demonstrated the potential of using unmanned aerial vehicles (UAV or drones) equipped with a high‐resolution video camera to provide density estimates (or at least encounter rates) of marine fauna with no or limited disturbance (Hodgson et al , , ; Kiszka et al , ).…”
Section: Introductionmentioning
confidence: 99%